Sosialisasi “Bahagia” Guna Meningkatkan Kemandirian dan Kualitas Hidup Golongan Lansia Di Rumah Bahagia Bintan - Meldawaty, Meldawaty (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Basically, the purpose of human life is to find comfort and happiness in life. Meanwhile, the aging process experienced by the elderly causes them to experience various kinds of feelings such as sadness, anxiety, loneliness, and irritability. The elderly are people who are aged 65 years and over; this age will distinguish someone who is still an adult or an elderly person. In the view of Indonesians, the elderly are people who are over 60 years old. More than 60 years, because generally in Indonesia it is used as the maximum working age and the signs of aging are starting to appear. Old age is part of the process of growth and development. Humans do not suddenly grow old; they develop from babies, children, and adults and eventually grow old. So that this doesn't happen, the elderly need various activities, such as counseling about the stages of growth and development of happy elderly people. After participating in the counseling process, the elderly are able to explain and understand the keys to being happy, useful, and quality elderly.